Euclid space mission: a cosmological challenge for the next 15 years. Issue Volume 10:Issue S306(2014) (1st July 2015) - Scaramella, R.; Mellier, Y.; Amiaux, J.; Burigana, C.; Carvalho, C.S.; Cuillandre, J.C.; da Silva, A.; Dinis, J.; Derosa, A.; Maiorano, E.; Franzetti, P.; Garilli, B.; et al.
Abstract: Euclid is the next ESA mission devoted to cosmology. It aims at observing most of the extragalactic sky, studying both gravitational lensing and clustering over 15, 000 square degrees. The mission is expected to be launched in year 2020 and to last six years. The sheer amount of data of different kinds, the variety of (un)known systematic effects and the complexity of measures require efforts both in sophisticated simulations and techniques of data analysis. We review the mission main characteristics, some aspects of the the survey and highlight some of the areas of interest to this meeting.